The Relationship Between Adolescents' Knowledge Level And Teacher Support on Compliance with Blood Supplement Tablets Consumption In SMP Negeri 3 Palangka Raya - Sitohang, Megawati; Widodo, Tri; Ahmad, Farah Fauziyah Radhiyatulqalbi; Lestarisa, Trilianty; Komara, Nisa Kartika (Fakultas Kedokteran Universitas Palangka Raya, 2025)
Indonesia has 20 provinces with anemia prevalence rates higher than the national average, with Central Kalimantan ranking third at 12.7%. This is due to a lack of awareness and knowledge about anemia among adolescent girls. SMP Negeri 3 is one of the schools in Central Kalimantan that receives blood supplement tablets (TTD). This study aims to analyze the relationship between the level of knowledge of adolescents and teacher support for TTD consumption compliance among seventh and eighth grade female students at SMP Negeri 3 Palangka Raya. The population in this study consisted of 344 female students in grades VII and VIII at SMP Negeri 3 Palangka Raya, with a sample size of 100 female adolescents. This study used an analytical observational method with data collection using a questionnaire with 32 questions. Respondents were selected based on Proportional Stratified Random Sampling, then data processing was carried out using the SPSS application using univariate analysis and bivariate analysis with the Spearman correlation test method. The results of the study indicate that there is a relationship between knowledge and compliance with taking Blood Supplement Tablets (TTD) among female students in grades VII and VIII at SMP Negeri 3 Palangka Raya, and that there is a relationship between teacher support and compliance with taking Blood Supplement Tablets (TTD) among female students in grades VII and VIII at SMP Negeri 3 Palangka Raya. The results of this study can be concluded that there is a significant positive relationship between the level of knowledge of adolescents and teacher support for compliance with blood supplement tablet consumption among female students in grades VII and VIII at SMP Negeri 3 Palangka Raya, with the strength of the relationship being strong and moderately strong, respectively.